Incidencia del desempleo en la inflación de Latinoamérica: un estudio con datos panel mediante técnicas de cointegración y causalidad, periodo 1991-2020. - Camaño Esparza, Gabriela Keisey (2022)
Inflation is a problem that is daily experienced in economy, during the last years it has been increasing from 2.69% (2016) to 3.20% (2020) worldwide, this problem generated by an increase in the general demand, while the supply of the productive sector is not able to face that demand consequently prices go up. Therefore, the general objective of this research is to examine the incidence of unemployment on inflation in Latin America through an econometric study using co-integration and causality with data panel, period 1991-2020. To carry out this research, there were used data panel collected from the World Bank (2020). Considering inflation as the dependent variable and unemployment as the independent variable, and money supply and workers' remittances as control variables. The methodology used includes an analysis of the examined variables’ evolution, a GLS model that determines the relation between the variables, a co-integration test to identify if there is short-term equilibrium and a causality test. The results show the existence of a positive and significant relation between unemployment and inflation. Furthermore, it is determined that there is no short-term relation, but it is negative, which does not comply with the Phillips curve theory. Based on these results, it is suggested to establish policies that help to reduce unemployment and improve the capabilities of the population in order to maintain inflation stability.